PERANCANGAN SISTEM PENGENDALIAN KUALITAS PROSES DI PT. VISTA MEGA JAYA - Dewo Setyo Panegoro; Arsyad Sumantika (Computer Science and Industrial Engineering, 2026)
PT Vista Mega Jaya, a company engaged in the fabrication of industrial, restaurant, and residential equipment, was identified as lacking quality control in the dome device table production process at PT Vista Mega Jaya. Based on the identified key issues, the objective of this study was to utilize the DMAIC method, one of the six sigma concept tools, to improve product quality by identifying the causes of product defects and developing proposed improvement plans. The DMAIC method can be used to reduce product defects occurring in the dome device table production process at PT Vista Mega Jaya. The results of the DMAIC study revealed that the average defect rate from January 2024 to December 2024 was 5.6%, with a sigma value of 2.4%, as the company aims for a defect rate of less than 3%. The largest number of defects occurred in the welding process. The lack of work process guidelines, disorganized workers, and inadequate maintenance led to a high number of defective products, necessitating rework. After implementing the improvement plan within four months, the dome device table production process achieved a sigma value of 3.57 out of 2.4.